'Do not go gentle into that good night': the Anthropecene and the cyclical time of human suffering. Issue 6 (18th August 2021) - Canefe, Nergis
ABSTRACT: This short essay explores the notions of ontological recognition in relation to ecological disasters, and examines possibilities for survival. It presents forced migration as an important aspect of the anthropocene and its consequences as suffering and death through the lens of time. The main argument draws on Dylan Thomas' poem to introduce the politics of the Anthoropocene and addresses the question of death beyond contemporary forms of understanding human suffering via the concept of the aporia of death.